Impacto dos equipamentos de proteção individual no desempenho dos trabalhadores em uma fábrica de metais pesados - Benelli, Matheus de Medeiros (Universidade Federal de São Carlos, 2023)
Personal Protective Equipment (PPE) is necessary in industry to prevent accidents and health problems. The objective of the research is to investigate the reasons why workers often fail to use PPE. The case study was carried out in a company located in Sorocaba, in the State of São Paulo, which has lead as one of its raw materials. The chosen research approach was mixed, and through this study it was identified that not all operators use PPE correctly, and that these PPE do not always help protect employees, specially if they are not designed and designed to individually meet the needs of all employees, according to their physiological characteristics and the working conditions in which they work.
Impact of personal protective equipment on worker's performance in a heavy metal factory
Keywords: Equipamentos de Proteção Individual; Ergonomia; Metais Pesados; Saúde do Trabalhador; Personal Protective Equipment; Ergonomics; Heavy Metals; Worker's Health; ENGENHARIAS::ENGENHARIA DE PRODUCAO